Handling Coffee Break Events in the Food and Beverage Service Department at Swiss-Belinn Hotel Gajah Mada Medan - Tinambunan, Erdi Sari (Cattleya Darmaya Fortuna, 2024)
A coffee break is a service provided during meeting intervals where guests are served coffee, tea, and snacks. Typically lasting between 10 to 20 minutes, coffee breaks are common in meetings, seminars, or training sessions. This research employs a descriptive qualitative method to obtain data through field observations, direct interviews, and literature review. The data were collected from 10 participants, consisting of 1 supervisor, 4 waiters, and 5 guests at Swiss-Belinn Gajah Mada Medan. The findings indicate that the execution of coffee break services at the hotel is still inadequate. Standard Operating Procedures (SOPs), particularly regarding the setup of tables and equipment, have not been properly implemented. The author recommends that supervisors take full responsibility for overseeing all events held at the hotel. Regular briefings should be conducted to reinforce the importance of following service and table arrangement SOPs. Moreover, increasing the number of staff in the Food and Beverage Service department is crucial to ensure a balanced workload and improve overall service quality to meet guest expectations.